2023
DOI: 10.3389/fimmu.2023.1128138
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on antibacterial characteristics of the multiple liver expressed antimicrobial peptides (LEAPs) in teleost fish

Abstract: Antimicrobial peptides are important components of the host innate immune system, forming the first line of defense against infectious microorganisms. Among them, liver-expressed antimicrobial peptides (LEAPs) are a family of antimicrobial peptides that widely exist in vertebrates. LEAPs include two types, named LEAP-1 and LEAP-2, and many teleost fish have two or more LEAP-2s. In this study, LEAP-2C from rainbow trout and grass carp were discovered, both of which are composed of 3 exons and 2 introns. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Notably, LEAP2 expression in T. ovatus is high in the liver, spleen, head kidney, and gills [ 9 ], whereas in O. mykiss , LEAP2A, and LEAP2B are constitutively expressed only in the liver [ 8 ]. Our investigation revealed that following A. hydrophila infection, A. fasciatus LEAP2 expression is upregulated in all examined tissues, consistent with previous studies on other fish species [ 8 12 , 14 , 16 , 18 , 19 , 22 , 23 ]. For example, in B. pectinirostris , the liver, spleen, kidney, and gills exhibit an immediate increase in LEAP2 expression upon E. tarda infection [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, LEAP2 expression in T. ovatus is high in the liver, spleen, head kidney, and gills [ 9 ], whereas in O. mykiss , LEAP2A, and LEAP2B are constitutively expressed only in the liver [ 8 ]. Our investigation revealed that following A. hydrophila infection, A. fasciatus LEAP2 expression is upregulated in all examined tissues, consistent with previous studies on other fish species [ 8 12 , 14 , 16 , 18 , 19 , 22 , 23 ]. For example, in B. pectinirostris , the liver, spleen, kidney, and gills exhibit an immediate increase in LEAP2 expression upon E. tarda infection [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…[80,81], between the proteomes of high and low bacteriostatic plasma. Therefore, it is of further interest to investigate the rainbow trout plasma proteome to identify antimicrobial peptide precursor sequences that exhibit antimicrobial activity [82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%